Innovative Exemplars and Curriculum Created from Online Videos of Visual Artists in Greater Sudbury - Browning, Kathy (Journal of the Canadian Association for Curriculum Studies, 2018)
The article begins with a description of the award-winning online artists’ video project, 14 Videos of Visual Artists in Greater Sudbury, and concludes with a presentation of my pre-service BEd students’ creative use of this digital resource. The video series was conceived and created with the aim of filling a gap in materials that were sorely lacking to teachers of Visual Arts in Ontario. The video series includes Aboriginal, Métis, Francophone and Anglophone artists and highlights the artists’ interconnections with the local community. The streamed, linked and library-accessible videos (see http://www3.laurentian.ca/visual_artists/) served as inspiration for student teachers’ creation of their own innovative curricular exemplars. In the article, I describe the complex inner workings of the research project in order to establish a context for the students’ work. I show how the students were able to conceptualize curriculum through being able to better see what and how to teach through creating art and making exemplars in a variety of media. Using the artists’ work as a catalyst, the students worked in groups, selecting artists whose artwork spoke to them while creating exemplars and co-creating curricula that would be meaningful. The article concludes with student exemplars that offer insights into the value of focusing on local artists in order to better meet Art Education curriculum goals in Ontario and, by extension, elsewhere in Canada.